2010
DOI: 10.1016/j.neuron.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 2 Regulates the NR2 Subunit Composition of Synaptic NMDA Receptors

Abstract: SUMMARY NMDA receptors (NMDARs) play a central role in development, synaptic plasticity and neurological disease. NMDAR subunit composition defines their biophysical properties and downstream signaling. Casein kinase 2 (CK2) phosphorylates the NR2B subunit within its PDZ-binding domain; however, the consequences for NMDAR localization and function are unclear. Here we show that CK2 phosphorylation of NR2B regulates synaptic NR2B and NR2A in response to activity. We find that CK2 phosphorylates NR2B, but not NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
203
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(221 citation statements)
references
References 70 publications
17
203
0
1
Order By: Relevance
“…Neurons overexpressing GFP-GluN2A or GFP-GluN2B constructs, which were characterized previously and showed a similar function to those of endogenous GluN2A/2B subunits (24), were stimulated by 50 M NMDA on DIV 9. We chose DIV 9 neurons to examine the direct effect of GluN2A overexpression on neuronal death because the expression level of endogenous GluN2A was low and almost undetectable at this age (data not shown).…”
Section: Volume 288 • Number 33 • August 16 2013mentioning
confidence: 71%
“…Neurons overexpressing GFP-GluN2A or GFP-GluN2B constructs, which were characterized previously and showed a similar function to those of endogenous GluN2A/2B subunits (24), were stimulated by 50 M NMDA on DIV 9. We chose DIV 9 neurons to examine the direct effect of GluN2A overexpression on neuronal death because the expression level of endogenous GluN2A was low and almost undetectable at this age (data not shown).…”
Section: Volume 288 • Number 33 • August 16 2013mentioning
confidence: 71%
“…It is hence feasible that in moonwalker mice lack of phosphorylation of the channel protein leads to aberrant translocation of more channel protein to the plasma membrane, resulting in larger whole cell currents in moonwalker than wild type mice. Alternatively, it could be that the moonwalker phosphorylation site controls subunit composition of the DHPG-activated TRPC channel, as was demonstrated for synaptic NMDA receptors (44). In this model lack of phosphorylation of the moonwalker DHPG-activated channel would result in insertion of TRPC channels with a distinct subunit composition, resulting in altered channel properties.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, the present study provides the first evidence that phosphorylation of one tyrosine site regulates the phosphorylation of another in the GluN2B subunit. In addition, a recent study reported that Ser-1480 on GluN2B is also involved in the modulation of Tyr(P)-1472 levels (43), implying that regulation of Tyr-1472 is complicated. Given multiple tyrosine sites on GluN2B identified to be phosphorylated by Fyn, an intriguing question remaining to be addressed is how the phosphorylation of these sites is differentially regulated by Fyn during specific synaptic activities.…”
Section: Discussionmentioning
confidence: 99%